2014
DOI: 10.1111/jog.12417
|View full text |Cite
|
Sign up to set email alerts
|

Self‐control study on reduced‐dose depot versus daily administration of gonadotrophin‐releasing hormone agonists for pituitary desensitization in in vitro fertilization cycles

Abstract: Reduced-dose depot GnRH-a can be successfully used for pituitary desensitization in in vitro fertilization and embryo transfer. Deeper downregulation with reduced-dose depot GnRH-a indicates that the optimal dose of GnRH-a warrants future study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It has been noted that clinical pregnancy rate might increase when patients are given a period of artificial amenorrhea caused by GnRH-a (Cai et al, 2018; Liao et al, 2015; Martínez et al, 2014; Ren et al, 2014). One full-dose depot of long-acting GnRH-a per COH cycle would be more convenient for women than short-acting GnRH-a injections because there are fewer injections, leading to greater compliance as well as fewer incidences of infection (Cheon et al, 2008; Gao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that clinical pregnancy rate might increase when patients are given a period of artificial amenorrhea caused by GnRH-a (Cai et al, 2018; Liao et al, 2015; Martínez et al, 2014; Ren et al, 2014). One full-dose depot of long-acting GnRH-a per COH cycle would be more convenient for women than short-acting GnRH-a injections because there are fewer injections, leading to greater compliance as well as fewer incidences of infection (Cheon et al, 2008; Gao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…GnRHa long protocol has longer and deeper pituitary downregulation compared to GnRHa short protocol. Longer pituitary downregulation significantly increased the number of mature oocytes [ 27 ], implantation rate, the number of good-quality embryos [ 28 ], clinical pregnancy rate, and live birth rate [ 29 ]. Recent studies support that longer pituitary downregulation favors ART outcomes regardless of age or ovarian response.…”
Section: Discussionmentioning
confidence: 99%
“…Gonadotropin releasing hormone agonist (GnRH-a) remains the most commonly-used peptide hormone in COH during ART treatments because it can obtain the most oocytes, prevent early-onset LH peaks, reduce luteinization, and improve cycle completion rates (Haydardedeoğlu & Kılıçdağ, 2016). Patients that have been treated with long-acting GnRHa during COH have shown good compliance and clinical pregnancy rates (Gao et al, 2014;Liao et al, 2015). Our previous study also showed encouraging clinical outcomes for long-acting GnRH-a, regardless of the patient's menstrual cycle time (Ying et al, 2019).…”
Section: Introductionmentioning
confidence: 99%